The leper of Saint Giles - Peters, Ellis, 1913-1995 (Peters, Ellis, 1913-1995. Chronicles of Brother Cadfael, 2017)
Brother Cadfael must travel to the heart of a leper colony to root out the secret to a savage murder. Setting out for the Saint Giles leper colony outside Shrewsbury, Brother Cadfael has more pressing matters on his mind than the grand wedding coming to his abbey. But as fate would have it, Cadfael arrives at Saint Giles just as the nuptial party passes the colony's gates. He sees the fragile bride looking like a prisoner between her two stern guardians and the bridegroom--an arrogant, fleshy aristocrat old enough to be her grandfather. And he quickly discerns this union may be more damned than blessed. Indeed, a savage murder will interrupt the May-December marriage and leave Brother Cadfael with a dark, terrible mystery to solve. For the key to the killing--and a secret--are hid among the lepers of Saint Giles. Now Brother Cadfael's skills must ferret out a sickness, not of the body, but of a twisted soul.